Integration of ICT into education: lessons learnt at the State University of Zanzibar and the Midlands State University in Zimbabwe - Pondiwa, Shephard; El Nabahany, Umayra; Phiri, Margaret (IntechOpen, 2022)
The provision of education using ICT has been adopted by many institutions in Africa. The use of ICT is critical in knowledge-based societies such as those in Zanzibar and Zimbabwe. This study looks at how the Midlands State University (MSU) and State University of Zanzibar (SUZA) have adopted the use of ICT in many ways. ICTs do not work for everyone in the same way. It has become inevitable, in the current digital era for educators to integrate ICT in their teaching and gradually replace traditional teaching methods with modern ones which are ICT led. The main objective of this study is to find out challenges and opportunities of using ICT in education.